Cyclooxygenase‐2 inhibition partially protects against 60% O2‐mediated lung injury in neonatal rats. Issue 10 (23rd November 2013) - Masood, Azhar; Yi, Man; Lau, Mandy; Belcastro, Rosetta; Li, Jun; Kantores, Crystal; Pace‐Asciak, Cecil R.; Jankov, Robert P.; Tanswell, A. Keith
Summary Rationale Use of the anti‐inflammatory agent dexamethasone in premature infants with bronchopulmonary dysplasia has been curtailed, and no alternative anti‐inflammatory agents are approved for this use. Our objective was to use a neonatal rat model of bronchopulmonary dysplasia to determine if an highly selective cyclooxygenase‐2 inhibitor, 5, 5‐dimethyl‐3‐(3‐fluorophenyl)4‐(4‐methylsulfonyl)phenyl‐2(5H)‐furanone (DFU; 10 µg/g body weight), could prevent inflammatory cell influx and protect against lung injury. Methods Neonatal rats exposed to air or 60% O2 for 14 days from birth either received daily i.p. injections of (i) vehicle or DFU or (ii) vehicle or an EP(1) receptor antagonist, SC‐19220. Results DFU attenuated the lung macrophage and neutrophil influx, prevented interstitial thickening and prevented the loss of peripheral blood vessels induced by 60% O2, but did not protect against the variance in alveolar diameter induced by 60% O2. Exposure to 60% O2 caused both an increase in lung prostaglandin E2 content and a reduction in lung mesenchymal cell mass which was reversed by DFU. Prostaglandin E2 binding to the EP(1) receptor inhibited DNA synthesis in cultures of lung fibroblasts in a dose dependent fashion. Treatment with SC‐19220 attenuated the reduction in lung mesenchymal mass observed following exposure of rat pups to 60% O2. Conclusions An highly selective cyclooxygenase‐2 inhibitor is an effective anti‐inflammatory substitute for dexamethasone for preventing phagocyte influx into the neonatal lung during 60% O2‐mediated lung injury, and can modify the severity of that injury. Pediatr Pulmonol. 2014; 49:991–1002. © 2013 Wiley Periodicals, Inc.